Age and Downward Mobility: From the Poorhouse to the Present. Issue 2 (4th May 2021) - Wagner, David
ABSTRACT: This article provides an overview of the problem of poverty and downward mobility for the elderly in the United States from the 19th Century to today. Using the author's research with the history of poorhouses (also known as poor farms, workhouses, almshouses, and later county homes and hospitals) he describes the situation of many older people as they faced poverty, family estrangement, personal loss, and medical problems. Looking to provide a brief comparison to our past and current situation, Wagner summarizes a set of statistics about the elderly in the 21st century including low income, low savings for retirement, and lack of adequate health care to suggest that while there have been a few improvements, on the whole a majority of elderly people face the same and similar serious issues as did our forerunners.